Perencanaan Dan Pengembangan Bisnis Dalam Era Transformasi Digital - Bimo Dwi Pasa; Farrel Apta Kassuma Putra; Naufal Arsyad; Maharani Ikaningtyas; Rusdi Hidayat (Jurnal Manajemen Kreatif dan Inovasi, 2024)
In the midst of the rapid flow of globalization, there is one sector that continues to follow the flow, namely the economic sector. Economic development that expands into a global scale is directly under the development of digital technology which directly impacts changes in business implementation, the company's ability to improve the quality of performance, and encourage company performance in innovating in business, the method used by the author is descriptive with qualitative techniques.